1991
DOI: 10.1148/radiology.181.1.1887044
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced muscle modifications: study of healthy subjects and patients with metabolic myopathies with MR imaging and P-31 spectroscopy.

Abstract: Exercise-induced variations in proton signal intensity at magnetic resonance (MR) imaging and in intracellular pH were studied in the forearm muscles of healthy subjects and patients with muscular glycogenoses. The relative increase in T2 was measured from MR images obtained at 0.5 T, and end-exercise pH was measured with surface coil phosphorus-31 spectroscopy at 2 T. Eight healthy subjects showed a relative increase in T2 ranging from 20% to 44% in the flexor digitorum superficialis muscle and a drop in pH r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…While changes in muscle volume as a factor involved in post-exercise T2 changes have been refuted on the basis of venous occlusion experiments [131], it has been clearly demonstrated that T2 changes were graded with exercise intensity during dorsiflexion exercises [130], thereby indicating that T2 changes during exercise are dependent on the force generated. Besides these observations, a direct relationship between changes in osmotically active metabolites such as lactate and P i has also been correlated with the extent of T2 changes [132,133], indicating that they are likely related to osmotically driven fluid shift. This relationship between the extent of T2 and pH changes in exercising muscle has been confirmed from a functionnal analysis of McArdle patients.…”
Section: T2 and Metabolic Changesmentioning
confidence: 82%
“…While changes in muscle volume as a factor involved in post-exercise T2 changes have been refuted on the basis of venous occlusion experiments [131], it has been clearly demonstrated that T2 changes were graded with exercise intensity during dorsiflexion exercises [130], thereby indicating that T2 changes during exercise are dependent on the force generated. Besides these observations, a direct relationship between changes in osmotically active metabolites such as lactate and P i has also been correlated with the extent of T2 changes [132,133], indicating that they are likely related to osmotically driven fluid shift. This relationship between the extent of T2 and pH changes in exercising muscle has been confirmed from a functionnal analysis of McArdle patients.…”
Section: T2 and Metabolic Changesmentioning
confidence: 82%
“…The robust (up to ϳ30%; Ref. 16) changes in SI that occur during and after exercise are intensity dependent (14) and relate directly to electromyographic measures of motor unit activation (1). The inherent spatial localization capability of MRI means that muscle utilization can be evaluated in both superficial and deep muscles with in-plane resolutions of Ͻ10 mm 2 by using EPI or Ͻ5 mm 2 by using conventional spin-echo imaging.…”
Section: Discussionmentioning
confidence: 99%
“…T 2 is inversely related to intracellular pH (pH i ) in chemically-skinned rabbit psoas muscle (12) and in isolated rat liver (13). End-exercise pH i and T 2 are also correlated (2,14); however, during incremental arm ergometer exercise, pH i changes lag T 2 changes, and during recovery from this exercise, pH i recovers more quickly than T 2 (15). Together, these findings imply that pH i changes may contribute to, but cannot be the sole cause of, the T 2 increase during exercise.…”
mentioning
confidence: 99%